(untitled) (CIPEEX, 2025)
The current study aims to analyze the relationship between breastfeeding and breast cancer prevention, highlighting the biological mechanisms involved and the benefits for women’s health. Breast cancer is the second leading cause of death among women and results from the uncontrolled proliferation of cells that acquire atypical characteristics, which can spread to other parts of the body, resulting in metastases. Making it one of the most significant health challenges of women around the world. Breast cancer control is a priority in Brazil’s health policy and has been recognized as one of the goals of the Health Pact. Given the high incidence and mortality associated with breast cancer, especially in women aged 45 to 50 years, the prevention and control of this disease, access to diagnosis and treatment in an appropriate time and others, are priorities in Brazilian health policy. The National Cancer Institute reported new cases of breast cancer are increasing annually. It is estimated that between 2023 and 2025, around 66.54 cases will occur for every 100,000 women, totaling around 73,610 new diagnoses. The disease is complex, influenced by genetic factors, lifestyle, reproductive history and environment. In this context, breastfeeding stands out as an important prevention strategy. In addition to the nutritional and emotional benefits for the baby, it has biological mechanisms that contribute significantly to reducing the risk of breast cancer in the mother, being associated with the reduction in the levels of certain hormones such as Estrogen and Progesterone, which are linked to increased risk of cancer. During breastfeeding, breast cells with mutations are also eliminated, and the macrophages present in milk play an important role in the destruction of neoplastic cells, strengthening the body’s natural defense. The Ministry of Health warns that breastfeeding can reduce the risk of breast cancer by up to 6% per year, preventing almost 20 thousand deaths annually, with the potential to prevent another 20 thousand deaths with best breastfeeding practices. The study method is an integrative literature review, analysis of scientific articles in the databases: PubMed, LILACS, Bireme, Scielo, publications from the Ministry of Health and academic repositories. The results indicate that breastfeeding, especially when exclusive and prolonged, not only promotes infant health, but is also an important protective factor in preventing breast cancer. Thus, breastfeeding offers a wide range of benefits for both mother and baby. It is concluded that breastfeeding plays an essential role in preventing CA, with the biological mechanisms that protect women against this disease. Encouraging and actively supporting breastfeeding not only improves child health, but is also an effective public health strategy in reducing the incidence of breast cancer. Therefore, it is imperative that health policies prioritize the promotion of breastfeeding, offering ongoing support and education to mothers about the lasting benefits of this habit.